In Vitro Dissolution of Inorganic Phosphates Using Certain Root Zonebacteria Associated With the Roots of Different Plants - Shler, Ali Khorsheed (International Journal of Life Science and Pharma Research, 2025)
Degradation, mobilization nutrient, mineralization, solubilization, nitrogen fixation, and growth hormone synthesis are among the soil processes that are mediated Via (PGPR). As result developing organic acids, microorganisms with the ability to solubilize phosphates can change insoluble phosphates into soluble forms. Phosphorus deficit may be mitigated by the promising method of inoculating seeds with P-solubilizing bacteria. The availability From the soil Soil phosphorus around roots differs substantially based Upon the plantspecies and soil nutrition. Derived from 251 bacterial isolates were Extracted Starting at the roots of three different plants Legumes such as chickpeas, lentils, and beans grown in Kirkuk, Erbil .In overall, there were (128)isolates Associated with plant growth-promoting rhizobacteria in Kirkuk &123) isolates in Erbil (though only 54 of these isolates Evaluated for different plant growth-promoting traits were selected and detected. A total of 54 isolates were investigated In vitro phosphate solubilization by these isolates in legumes. According to Bergey’s Manual, the overall percentages of isolates were Pseudomonas spp (34%), Enterobacter spp (31%), Legionella beijerinckiaspp (10%), Bacillus spp (8%), Nitrobacterspp (8%), Nitrosomonasspp (3%), Paenibacillus (3%), Actinomycetes (1%), Frankia (1%), Mycxobacteriaspp (1%), Closttridumspp (1%), Actinobacillus (1%).